Does student's critical thinking and collaboration skills can empower through investigation and thinking learning strategy? - Lina Listiana; Nadiya Mutiara Loka; Yuni Gayatri (University of Muhammadiyah Malang, 2023)
The low critical thinking skills and collaboration skills of students in biology learning are caused by the dominance of conventional learning, so they require alternative learning strategies. This study aims to determine the effect of GITTW learning strategy on student critical thinking and collaboration skills. The research design used was quasi-experiment with a pre-test and post-test control group design. The class X of Science-2 and of Science-3 SMA Negeri 01 Paciran became sample (N=72), with details; the control class and treatment class consisting of 36 students. Data collection critical thinking skills using easy test before and after treatment with Facione rubric developed and data collaborative skills using observation sheet assessment rubric developed by Suharti. Data were analyzed descriptively and statistically through normality test, Wilcoxon test with =0.05, and N-gain test. The results showed that the GITTW learning strategy had an effective effect, and can be applied by the teacher as an alternative learning strategy.